A geochemical and morphological investigation of placer gold grains from the southern Seward Peninsula, Alaska : implications for source and transport mechanisms - Gauntlett, Ernest John Herbert (Rhodes University, Faculty of Science, Department of Geology, 2015)
[Partial abstract]: This study presents the first detailed geochemical and morphological characterisation of gold grains from the southern Seward Peninsula, Alaska, a region with significant historical and on-going placer gold mining. Quantitative Au, Ag, Hg, and Cu data are presented for gold grains from eleven sites. Additionally, quantitative Te, W, As, and Sb trace element data are presented for gold grains from ten of the eleven sites. Although it is acknowledged that quantitative trace element analysis of gold grains is a relatively new endeavour, the limited trace element data obtained in this study suggest that trace element analysis could be useful for characterising gold sources on the southern Seward Peninsula. Major and minor element geochemical profiling is sufficient at differentiating between sites from regional provenance systems but insufficient at differentiating between sites within a single system. Differentiating among sites within a single system will likely require microchemical analysis of mineral inclusions and analysis of trace element signatures.
Keywords: Placer deposits -- Alaska -- Seward Peninsula; Gold alloys; Gold mines and mining -- Alaska -- Seward Peninsula; Geochemical surveys -- Alaska -- Seward Peninsula; Trace elements -- Alaska -- Seward Peninsula; Drift -- Alaska -- Seward Peninsula; Gold -- Standards of fineness